The emergence of mindfulness acceptance commitment for psychological enhancement during covid-19 pandemic - Nur Haziyanti Moahamad Khalid; Muhammad Idris Bullare @ Bahari (Ubiquity Press, 2020)
This paper aims to shed light on the conceptual framework of the emergence of Mindfulness Acceptance Commitment (MAC) training module for psychological enhancement during COVID-19 pandemic. This module known as MAC-COVID-19 is intended for providing knowledge of MAC to community in order to deal with stress symptoms caused by COVID-19 pandemic; provide systematic guidelines using MAC skills training; help community to maintain healthy mindset in response to the COVID-19 pandemic risk factors; and help community to achieve resiliency. The training contained in this module is based on self-help intervention. It is in line with the social distancing practiced by the community during the COVID-19 pandemic. It is hoped that this training module will benefit the community, helping them to deal with the psychological distress caused by the pandemic.